Argon–Helium Cryoablation for Cutaneous Squamous Cell Carcinoma in the Elderly - Huang, Qianwen; Xu, Wenshen (Frontiers in Oncology, 2022)
Cutaneous squamous cell carcinoma (cSCC) is a common type of malignant neoplasm in non-melanoma skin cancer (NMSC). Most simple cSCC cases are considered curable by surgical removal of the lesion. However, clinical treatments for cSCC with medium- or large-size lesions are difficult. Meanwhile, the effectiveness of the treatments is not guaranteed, especially for the elderly patients due to the intolerance of surgical resection or other adjuvant modality. In such cases, safe and effective treatments with excellent aesthetic outcomes are urgently need. In this study, we reported 6 elderly cSCC cases with medium- or large-size lesions treated with argon-helium cryoablation. The average age of all 6 patients was 78 years (range 72-85). They were all diagnosed with cSCC with median tumor size of 5.8 cm (range 2.5-15.5) and dermal invasion. Complete ablation was achieved in all cases after a single ablation session (2 freeze-thaw cycles). There was mild pain after ablation that was tolerable. One case developed infection and fever due to extensive necrosis of tumor, and was eventually cured after treatment. All patients obtained good cosmetic outcome, and the quality of life was significantly improved. In the 5 year follow-up study, 4 patients were alive, meanwhile, 2 patients were died due to unrelated diseases 3 years after cryotherapy. None of the 6 patients had recurrence. These results suggested the use of argon-helium cryoablation as a novel therapeutic strategy for elderly cSCC with medium- or large-size lesions.